Breast carcinoma cells modulate the chemoattractive activity of human bone marrow‐derived mesenchymal stromal cells by interfering with CXCL12. Issue 1 (20th May 2014) - Wobus, Manja; List, Catrin; Dittrich, Tobias; Dhawan, Abhishek; Duryagina, Regina; Arabanian, Laleh S.; Kast, Karin; Wimberger, Pauline; Stiehler, Maik; Hofbauer, Lorenz C.; Jakob, Franz; Ehninger, Gerhard; et al.
<x xml:space="preserve">Abstract</x> We investigated whether breast tumor cells can modulate the function of mesenchymal stromal cells (MSCs) with a special emphasis on their chemoattractive activity towards hematopoietic stem and progenitor cells (HSPCs). Primary MSCs as well as a MSC line (SCP‐1) were cocultured with primary breast cancer cells, MCF‐7, MDA‐MB231 breast carcinoma or MCF‐10A non‐malignant breast epithelial cells or their conditioned medium. In addition, the frequency of circulating clonogenic hematopoietic progenitors was determined in 78 patients with breast cancer and compared with healthy controls. Gene expression analysis of SCP‐1 cells cultured with MCF‐7 medium revealed CXCL12 (SDF‐1) as one of the most significantly downregulated genes. Supernatant from both MCF‐7 and MDA‐MB231 reduced the CXCL12 promoter activity in SCP‐1 cells to 77% and 47%, respectively. Moreover, the CXCL12 mRNA and protein levels were significantly reduced. As functional consequence of lower CXCL12 levels, we detected a decreased trans‐well migration of HSPCs towards MSC/tumor cell cocultures or conditioned medium. The specificity of this effect was confirmed by blocking studies with the CXCR4 antagonist AMD3100. Downregulation of SP1 and increased miR‐23a levels in MSCs after contact with tumor cell medium as well as enhanced TGFβ1 expression were identified as potential molecular regulators of CXCL12 activity in MSCs. Moreover, we observed a significantly higher frequency of circulating colony‐forming hematopoietic progenitors in patients with breast cancer compared with healthy controls. Our in vitro results propose a potential new mechanism by which disseminated tumor cells in the bone marrow may interfere with hematopoiesis by modulating CXCL12 in protected niches.